The Effectivity of Group Conseling on Improving Patient Behavior for Prevention Dpd - Mira Utami Ningsih; Abu Bakar; Makhfudli Makhfudli (Jurnal Ners, 2010)
Introduction: Dengue Hemorrhage Fever is a disease with prevalence that keep on higher and spread wider. Prevention and control of DHF are affected by environment and social-behavioral factors. So that, some efforts are needed to increase people awareness in prevention of DHF by giving health education. This study was aimed to fi nd out the difference effectiveness of elucidation and group counseling method to emendation of patriarch behavior in DHF prevention. Method: This study used pre-post test design. The population is patriarch in Monjok Pemamoran Village RT 01. Samples were 40 patriarchs taken by purposive sampling. Independent variables were elucidation and group counseling. Dependent variables were patriarch behavior including knowledge, attitude and practice. Data were collected using questionnaire and observation sheet then analyzed using Wilcoxon Signed Rank Test and Mann Whitney U-test.Result: The result revealed that there are significant effect of elucidation and group counseling to emendation of patriarch behavior in DHF prevention. Except in patriarch’s practice, there were no difference effectiveness of elucidation and group counseling to emendation of patriarch’s knowledge and attitude. There was difference effectiveness of elucidation and group counseling method to emendation of patriarch’s practice in prevention of DHF.Discussion: From this study in can be concluded that, both elucidation and group counseling can affect patriarch’s behavior in prevention of DHF but group counseling method is more effective. That’s why, it is hoped that paramedic can apply that method to society in purpose to increase prevention and control of DHF and prevents the outbreak.